2019
DOI: 10.21608/edj.2019.72859
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Failed Inferior Alveolar Nerve Block (IANB) in Achieving Pulpal Anaesthesia in Mandibular Molars with Symptomatic Irreversible Pulpitis

Abstract: Introduction: Patient comfort during root canal treatment is immense for patient cooperation and endodontist efficiency. Establishing the high prevalence of failure of IANB injections in providing pulpal anaesthesia, will most likely support the investigation of supplemental techniques to ensure patient comfort. Objectives: The study aimed to evaluate the prevalence of failed Inferior Alveolar Nerve Block (IANB) injections in achieving pulpal anaesthesia in mandibular molars diagnosed with symptomatic irrevers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…Successful anaesthesia is a hallmark of painless endodontic treatment. It not only keeps the patient calm and relaxed but also allows the dentist to perform the endodontic procedure with ease (Subbiya & Pradeepkumar, 2016;Howait & Basunbul, 2019). Pulpal anaesthesia commences with the administration of traditional nerve blocks (NBs) or infiltration anaesthesia.…”
Section: Introductionmentioning
confidence: 99%
“…Successful anaesthesia is a hallmark of painless endodontic treatment. It not only keeps the patient calm and relaxed but also allows the dentist to perform the endodontic procedure with ease (Subbiya & Pradeepkumar, 2016;Howait & Basunbul, 2019). Pulpal anaesthesia commences with the administration of traditional nerve blocks (NBs) or infiltration anaesthesia.…”
Section: Introductionmentioning
confidence: 99%
“…According to Iwanaga et al, 2018 andBhat et al, 2020, the most common mandible local anesthesia method is the inferior alveolar nerve blockage (IANB) (Iwanaga et al, 2018), (Bhat et al, 2020). A study by Rajvanshi, 2016 and Howait and Basunbul, 2019 showed a high efficiency of this method -85% (Rajvanshi H., Ernest S., Hafsa Effendi H., Afridi S., Chhabra M., 2016), (Howait M., Basunbul, 2019). The authors point out that the anesthesia success is an accurate hit in the pterygoid -maxillary space.…”
Section: Introductionmentioning
confidence: 99%